2019
DOI: 10.1111/os.12427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupoint Application Therapy with TianGui Powder on Osteoporosis in Ovariectomized Rats through TGF‐β1 and Smad2/3 Signaling Pathway

Abstract: Objectives To explore the effects of acupoint application therapy (AAT) with TianGui Powder (TGP) on the expressions of the transforming growth factor β1 (TGF‐β1) and Smad‐2/3 signaling pathway in ovariectomized osteoporosis rats. Methods Sixty rats were randomly divided into four groups: normal group (group A), model group (group B), TGP group (group C), and Western medicine group (group D). Group A had only the corresponding amount of adipose tissue around the ovary r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Recently, a series of studies found that interfering with the TGF-β signaling pathway can significantly affect the development of osteoporosis. Lin et al (2019) indicated that acupoint application therapy (AAT) using TianGui Powder (TGP) can prevent the progression of osteoporosis in ovariectomized rats by inhibiting the TGF-β/Smad2/3 signaling pathway. Song et al (2015) revealed that sulfuretin induces osteoblast differentiation by activating the TGF-β/Smad2/3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a series of studies found that interfering with the TGF-β signaling pathway can significantly affect the development of osteoporosis. Lin et al (2019) indicated that acupoint application therapy (AAT) using TianGui Powder (TGP) can prevent the progression of osteoporosis in ovariectomized rats by inhibiting the TGF-β/Smad2/3 signaling pathway. Song et al (2015) revealed that sulfuretin induces osteoblast differentiation by activating the TGF-β/Smad2/3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the late stage, TGF-β can regulate the collagen secretion and calcium salt deposition of osteoblasts [17]. In addition, Lin's team found that there is abundant expression of Smad2 protein in normal bone tissue, it is widely expressed in the epiph-ysis, and it is mainly expressed in osteoblasts on the surface of bone matrix and around trabecular bone [18]. TGF-β/Smad2 signal transduction is a rather complicated process from cell membrane to nucleus; the main steps include activation binding stage, recombination separation stage, and transfer action stage, involving many genes and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It applies Chinese herbal medicines to the skin at corresponding acupoints and has superior efficacy and fewer side effects than using Western medicine alone. [ 18 ] Our previous studies observed that SHP can improve gastrointestinal toxicity, intestinal mucosal damage induced by chemotherapy. [ 7 , 19 , 20 ] Each herb in SHP has been verified to regulate intestinal function, promote the increase of probiotics in the intestine, reduce the inflammation of the smooth muscle of the small intestine and accelerate the secretion of serum Ghrelin.…”
Section: Discussionmentioning
confidence: 99%